Sustainable, resource efficient informal settlements: assessing the role of co-design in informal settlement upgrading - Achi, Juliana Owot (My University, 2021)
Addressing climate change demands the promotion of sustainability in the formal and informal cities. However, sustainability interventions are widely critiqued for marginalising and neglecting the informal city. This study considers how co-design could enable spatial practitioners to harness informal design and construction tactics in the development of contextually responsive and sustainable solutions. It investigates the sustainability of design and construction practices in informal settlements and the effectiveness of co-design processes that draw from them to upgrading. It involved conducting of interviews, document analysis and observations of co-design workshops and informal design and construction tactics in a meta-analysis of five informal settlements. The application of sustainability practices such as recycling observed in the case studies, was mainly motivated by conditions of poverty, and co-existed with unsustainable conditions. However, through co-design processes, some interveners were able to harness informality in the development of contextually responsive, sustainable solutions
A research report submitted to the School of Architecture and Planning, University of the Witwatersrand, for the degree of Master of Urban Studies in the field of Sustainable Energy Efficient Cities, 2021